Biomechanical and physiological load carrying efficiency of two firefighter harness variations. Issue 1 (1st January 2018) - Kakar, Rumit Singh; Tome, Joshua M; King, Deborah L.; Jin, Zhongmin
Abstract: Firefighters and military personnel employ multiple backpack designs for carrying air tanks along with other heavy gear for occupational purposes. As the load increases, the biomechanical and physiological demands on the carrier change as well. The xPk® harness, a new design, claims to improve the load carriage ability for firefighters by allowing the load to be carried closer to the individual's center of mass (COM) thus reducing the energy cost and increasing comfort level compared with the traditional design. The study compared biomechanical and physiological differences during walking at 1.79m/s (4 mph) at different grades, while carrying a firefighter air tank in traditional harness to xPk® double strap harnesses. There were significant differences in grade kinematics, but differences between old and new harnesses were minor. The minimal differences and subjective preference for xPk® could potentially be helpful in improving load carrying capacity without having to retrain carrying mechanics.